The dissociable RPB4 subunit of RNA Pol II has vital functions in Drosophila. - Pankotai, T.; Ujfaludi, Z.; Vámos, E.; Suri, K.; Boros, I.M. (Molecular Genetics and Genomics, 2010)
RNA polymerase II (Pol II) is composed of a ten subunit core and a two subunit dissociable subcomplex comprising the fourth and seventh largest subunits, RPB4 and RPB7. The evolutionary highly conserved RPB4/7 heterodimer is positioned in the Pol II such that it can make contact with various factors involved in RNA biogenesis and is believed to play roles both during the process of transcription and post-transcription. A detailed analysis of RPB4/7 function in a multicellular eukaryote, however, is lacking partly because of the lack of a suitable genetic system. Here, we describe generation and initial analysis of Drosophila Rpb4 mutants. In the fly, RPB4 is a product of a bicistronic gene together with the ATAC histone acetyltransferase complex constituent ADA2a. DmAda2a and DmRpb4 are expressed during fly development at different levels. The structure of mature mRNA forms suggests that the production of DmADA2a and DmRPB4-specific mRNAs is ensured by alternative splicing. Genetic analysis indicates that both DmRPB4 and DmADA2a play essential roles, because their absence results in lethality in early and late larval stages, respectively. Upon stress of high temperature or nutritional starvation, the levels of RPB4 and ADA2a messages change differently. RPB4 colocalizes with Pol II to several sites on polytene chromosomes, however, at selected locus, the abundances of Pol II and RPB4 vary greatly. Our data suggest no tight functional link between DmADA2a and DmRPB4, and reveal differences in the abundances of Pol II core subunits and RPB4 localized at specific regions on polytene chromosomes, supporting the suggested role of RPB4 outside of transcription-engaged Pol II complexes.